The effect of the menstrual cycle on physical characteristics (speed, strength, and endurance) in women in Saudi Arabia - Alnefaie, Zayed M.; Albanna, Alanoud K.; Almuwallad, Ayah A.; Atallah, Sara M.; Abutowaimah, Shahad E.; Ibrahim, Ghala D.; Shahan, Nusayba A. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
The increasing participation of women in sports has raised interest in understanding how the menstrual cycle, specifically estrogen, progesterone, follicle-stimulating hormone (FSH), and luteinizing hormone (LH), affects athletic performance. These hormones fluctuate throughout the menstrual cycle, which is divided into the early follicular phase, ovulatory period, and mid-luteal phase, each with distinct hormonal profiles. While estrogen is believed to have an anabolic effect on skeletal muscle and influence substrate metabolism, progesterone may have an antiestrogenic effect, potentially affecting physical performance. However, research on the impact of these hormone fluctuations on performance yields contradictory results. Some studies report improved performance during various menstrual cycle phases, while others find no significant differences. Additionally, the effects of oral contraceptives (OCPs) on muscle strength and function remain unclear. Menopause, characterized by a decline in skeletal muscle mass and bone density, is associated with reduced physical performance in women. More research is needed to understand the effects of estrogen and progesterone fluctuations on physical performance in women, emphasizing the importance of gender-specific research and guidelines for optimizing athletic performance.